Czech Republic: Limited Constitutional Fiscal Policy and Public Finance Regulation - Radvan, Michal; Tomášková, Eva (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter focuses on the fiscal policy in the Czech Republic. It introduces the theoretical approach to public finance according to leading authors and experts in the field. From the legal perspective, it is necessary to highlight the constitutional foundations of public finance and budgetary institutions. However, public finance does not have a crucial role in the Czech Constitution and is not regulated in the Constitution in detail. The following section deals with the budget law, which is strongly connected to state fiscal policy. While fiscal policy as such is the responsibility of the entire government, the central state body upon which attention is focused in the area of public budgets is the Ministry of Finance. The most important laws in the area of fiscal policy include laws on the state budget and budgetary rules for the state budget and local self-government budgets. These are complemented by laws on the issuance of state bonds and the state bond programme. Most recently, the Act on the Rules of Budgetary Responsibility was introduced to regulate fiscal policy. The chapter presents several insights into state debt issues and fiscal deficits. It also analyses the Czech Republic’s crisis management in the context of crisis management at the European Union level. Finally, the main findings are summarised, and several de lege ferenda recommendations are offered. Keywords: Czech fiscal policy, Czech public finance, Czech budget law, budgetary responsibility, state debt, fiscal deficit, crisis management in the Czech Republic